Assessing the Role of Professional Reference Groups in Shaping Ethical Standards in Financial Accounting Practices for Effective Service Delivery in Nigeria - David Isaiah; Aroyehun Odunola Hafsat; Mohammed Tijjani (Journal of Corporate Finance Management and Banking System, 2025)
This study aimed to assess the role of professional reference groups, specifically the Institute of Chartered Accountants of Nigeria (ICAN) and the Association of National Accountants of Nigeria (ANAN), in shaping ethical standards for financial accounting practices in Nigeria. The research identified critical issues regarding the effectiveness of these groups in establishing and enforcing ethical guidelines, which are essential for the integrity of financial reporting. The statement of the problem highlighted challenges such as inadequate enforcement mechanisms, limited resources, and the need for a more cohesive approach to ethical compliance among accountants. A quantitative research methodology was adopted, involving a structured questionnaire distributed to 751 accredited firms of chartered accountants in Nigeria. The sample size was determined using Taro Yamane's formula, ensuring a representative data collection process. The analysis revealed that professional reference groups significantly influence ethical standards and the behavior of accountants. Major findings indicated that while the ethical guidelines set by ICAN and ANAN are effective in promoting ethical behavior, enforcement challenges persist, undermining their impact. Additionally, the study found that these groups positively influence organizational culture, enhancing the accuracy and integrity of financial reporting. The conclusion emphasized the importance of strengthening enforcement mechanisms and continuous training for accountants to uphold ethical standards. Recommendations included improving enforcement practices, offering regular training programs, fostering collaboration with regulatory authorities, and promoting an ethical culture within organizations. By addressing these issues, professional reference groups can enhance their effectiveness and ensure greater compliance with ethical standards, ultimately contributing to the overall performance and trustworthiness of the accounting profession in Nigeria.